Interleukin-2 enhancer binding factor 2 interacts with the nsp9 or nsp2 of porcine reproductive and respiratory syndrome virus and exerts negatively regulatory effect on the viral replication - Wen, Xuexia (Virol J, 2017)
BACKGROUND: Porcine reproductive and respiratory syndrome virus (PRRSV) causes reproductive failures in sows and respiratory diseases in growing pigs, resulting in huge economic loss for the pig production worldwide. The nonstructural protein 9 (nsp9) and nonstructural protein 2 (nsp2) of PRRSV are known to play important roles in viral replication. Cellular interleukin-2 enhancer binding factor 2 (ILF2) participates in many cellular pathways and involves in life cycle of some viruses. In the present study, we analyzed the interaction of cellular ILF2 with the nsp9 and nsp2 of PRRSV in vitro and explored the effect of ILF2 on viral replication. METHODS: The interaction of ILF2 with the nsp9 or nsp2 of PRRSV was analyzed in 293FT cells and MARC-145 cells by co-immunoprecipitation (Co-IP) and the co-localization of ILF2 with the nsp9 or nsp2 of PRRSV in MARC-145 cell and pulmonary alveolar macrophages (PAMs) was examined by confocal immunofluorescence assay. The effect of ILF2 knockdown and over-expression on PRRSV replication was explored in MARC-145 cells by small interfering RNA (siRNA) and lentivirus transduction, respectively. RESULTS: The interaction of ILF2 with nsp9 or nsp2 was first demonstrated in 293FT cells co-transfected with ILF2-expressing plasmid and nsp9-expressing plasmid or nsp2-expressing plasmid. The interaction of endogenous ILF2 with the nsp9 or nsp2 of PRRSV was further confirmed in MARC-145 cells transduced with GFP-nsp9-expressing lentiviruses or infected with PRRSV JXwn06. The RdRp domain of nsp9 was shown to be responsible for its interaction with ILF2, while three truncated nsp2 were shown to interact with ILF2. Moreover, we observed that ILF2 partly translocated from the nucleus to the cytoplasm and co-localized with nsp9 and nsp2 in PRRSV-infected MARC-145 cells and PAMs. Finally, our analysis indicated that knockdown of ILF2 favored the replication of PRRSV, while over-expression of ILF2 impaired the viral replication in MARC-145 cells. CONCLUSION: Our findings are the first to confirm that the porcine ILF2 interacts with the nsp9 and nsp2 of PRRSV in vitro, and exerts negatively regulatory effect on the replication of PRRSV. Our present study provides more evidence for understanding the roles of the interactions between cellular proteins and viral proteins in the replication of PRRSV. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12985-017-0794-5) contains supplementary material, which is available to authorized users.